Optimization and qualification of the single molecule array digital immunoassay for IL-12p70 in plasma of cancer patients. (4th September 2018) - Gupta, Vinita; Kalia, Navdeep; Yadav, Mahesh; Noyes, Amy; Good, Jeremy; Hendricks, Robert; Xu, Wenfeng
Aim: Cytokine/chemokine levels can reflect the pharmacodynamics of checkpoint inhibitors. The single molecule array (Simoa) HD-1 is a sensitive next-generation immunoassay platform for quantification of low abundance proteins, with potential for cancer immunotherapy mechanism of action studies.Results: The Simoa IL-12p70 reagents, standard curve and test conditions were optimized for improved precision and linearity of dilution in plasma of cancer patients. The assay achieved a lower limit of quantification of 0.08 pg/ml, with 27/29 samples recording above lower limit of quantification, precision ≤20% CV and accuracy within 80–120%.Conclusion: Simoa enabled quantification of IL-12p70 at sub-pg/ml levels in cancer patients and was superior to Simple Plex™ and Aushon ® in overall performance. This study qualifies the user-modified IL-12p70 immunoassay to measure pharmacodynamic changes in plasma during cancer immunotherapy.